2015
DOI: 10.7448/ias.18.1.20126
|View full text |Cite
|
Sign up to set email alerts
|

Ending overly broad HIV criminalization: Canadian scientists and clinicians stand for justice

Abstract: In Canada, people living with HIV who do not disclose their HIV status prior to sexual acts risk prosecution for aggravated sexual assault even if they have sex with a condom or while having a low (or undetectable) viral load, they had no intent to transmit HIV, and no transmission occurred. In 2013, six distinguished Canadian HIV scientists and clinicians took ground-breaking action to advance justice by co-authoring the “Canadian consensus statement on HIV and its transmission in the context of the criminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Building on the important theme of stigma-reduction, Eisinger, Dieffenbach, and Fauci (2019, 452) note the legal implications of HIV undetectability and how conceptually U ¼ U: 'bridges the best of biomedical science with current concepts in behavioural and social science by removing the sense of fear and guilt that a person may be harming someone else, as well as the feeling of self-imposed and external stigma that many people with HIV experience'. In Canada-which has the shameful distinction of being a global leader in criminally prosecuting cases of alleged HIV non-disclosure-undetectability has emerged as a scientific construct that has recently entered into criminal law discourse (Kazatchkine, Bernard, and Eba 2015;Housefather 2019). This move speaks not only to the significance of undetectability as an important concept mobilised to help limit the overly broad use of the criminal law, but also to the broader point of how this scientific idea has gradually and differentially moved overtime across discursive communities.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the important theme of stigma-reduction, Eisinger, Dieffenbach, and Fauci (2019, 452) note the legal implications of HIV undetectability and how conceptually U ¼ U: 'bridges the best of biomedical science with current concepts in behavioural and social science by removing the sense of fear and guilt that a person may be harming someone else, as well as the feeling of self-imposed and external stigma that many people with HIV experience'. In Canada-which has the shameful distinction of being a global leader in criminally prosecuting cases of alleged HIV non-disclosure-undetectability has emerged as a scientific construct that has recently entered into criminal law discourse (Kazatchkine, Bernard, and Eba 2015;Housefather 2019). This move speaks not only to the significance of undetectability as an important concept mobilised to help limit the overly broad use of the criminal law, but also to the broader point of how this scientific idea has gradually and differentially moved overtime across discursive communities.…”
Section: Discussionmentioning
confidence: 99%
“…55 This statement has since been endorsed by more than 75 scientists and clinicians across Canada. 56 It must be acknowledged that many ACCESS participants will disclose their HIV status to sexual partners, thus will not be at risk of criminal charges regardless of condom use or viral profile. Disclosure practices are not measured within the ACCESS survey; however, a cross-sectional survey of treatment-experienced people living with HIV in Vancouver found that most (73%) of the participants self-reported disclosing their HIV serostatus to all new sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…Prison policies may affect access to medical care and reduce or encourage sexual violence in the incarcerated setting (Goyer 2002). Furthermore, while most examples in this article are from American and Canadian jurisdictions, HIV criminalization is a global phenomenon across more than seventy countries, many in the Western world (Dej and Kilty 2012;Grace 2015;Kazatchkine et al 2015).…”
Section: Hiv Criminalization: a Challenge For Criminologymentioning
confidence: 99%